THU0316 Frequency of Axial Spondyloarthropathy Among Patients Suffering from Fibromyalgia. A Magnetic Resonance Imaging Study Applying the Assessment of Spondylo-Arthritis International Society Classification Criteria. (9th June 2015) - Ablin, J.; Eshed, I.; Berman, M.; Aloush, V.; Wigler, I.; Caspi, D.; Likhter, M.; Sharabi, A.; Rom-Broyde, A.; Borok, S.; Levartovsky, D.; Wolman, Y.; et al.
Abstract : Background: Fibromyalgia Syndrome (FMS), considered the result of increased processing of pain by the central nervous system, is a non-inflammatory condition characterized by chronic, widespread musculoskeletal pain and tenderness.Axial spondyloarthritis (SpA) is a group of inflammatory joint disease primarily involving the sacroiliac joints and axial spine. Although FMS and axial SpA differ vastly in their pathogenesis, a considerable clinical overlap may exist between these conditions. Chronic nocturnal back pain and disturbed sleep may accompany either condition. The Assessment of Spondylo-Arthritis international Society (ASAS) has published updated classification criteria for axial SpA with an imaging and clinical arms. We have previously described an increased prevalence of secondary FMS among female SpA patients. Objectives: To evaluate the prevalence of axial SpA among FMS patients, utilizing the 2010 ASAS criteria (1). Methods: Patients suffering from FMS (ACR 1990 classification criteria) were recruited consecutively from a specialized FMS clinic. Patients were interviewed regarding the presence of SpA features, as defined by the ASAS group (IBP, arthritis, enthesitis, uveitis, dactylitis, psoriasis, Crohn's/colitis, good response to NSAIDS, family history of SpA) and underwent HLA-B27 testing and CRP measurement. MRI examinations of the sacroiliac joints were performed on a 1.5 T MRI unit using semicoronal T1 weighted, STIR and FSPGR pre- and post-contrast injection sequences. FMS severity was assessed by the FIQ and SF-36 questionnaires and physical examination of the tender points using a dolorimeter. SpA symptom severity was assessed by the BASDAI questionnaire Results: 99 unselected patients were recruited and MRI results were available for 74. Sacroiliitis, based on ASAS definition (2), was found among 7 patients, 7 of which fulfilled ASAS SpA classification criteria. 6 patients fulfilled the criteria based on sacroiliitis on imaging and SpA features, one additional patient fulfilled SpA criteria based on HLA-B27 positivity and additional SpA features. Conclusions: Imaging findings suggestive of inflammatory SpA were not uncommon among patients presenting with a clinical diagnosis of FMS. Definite sacroiliitis and ASAS criteria SpA positivity were diagnosed among 9.5% of patients and additional changes typical of SpA were frequent. These findings suggest that FMS may mask an underlying SpA, a diagnosis with important therapeutic implications. Physicians involved in the management of FMS should remain vigilant to the possibility of underlying inflammatory disorders and actively search for such co-morbidities. References: Sieper J et al. Ann Rheum Dis 2009;68:8(Suppl II):ii1–ii44 Rudwaleit M et al. Ann Rheum Dis 2009; 68(10):1520 Disclosure of Interest: J. Ablin Speakers bureau: Pfizer Inc., I. Eshed: None declared, M. Berman: None declared, V. Aloush: None declared, I. Wigler: None declared, D. Caspi: None declared, M. Likhter: None declared, A. Sharabi: None declared, A. Rom-Broyde: None declared, S. Borok: None declared, D. Levartovsky: None declared, Y. Wolman: None declared, D. Paran: None declared, M. Anouk: None declared, O. Elkayam: None declared